Lest we forget memory of totalitarism in Europe ; a reader for older secondary school students anywhere in Europe - Purves, Gillian; Courtois, Stéphane (Inst. for the Study of Totalitarian Regimes, 2013)
An illustrated collection of 30 remarkable life stories of people affected by totalitarianism from 16 European countries, containing photographs and facsimiles of documents. Contributions by 23 public and nongovernmental institutions, organisations, museums and memorials dealing with the totalitarian past of Europe, associated in the Platform of European Memory and Conscience. Includes a multimedia DVD containing 2:20 hours of documentary films from 6 countries (5 – 50 mins length, English subtitles or voiceover), the Reader in 3 e-book formats (.pdf, .mobi, .epub), two printable essays and a map. The purpose of the reader is to educate today's young generation about Europe's tragic totalitarian past and about the importance of upholding fundamental human rights, freedoms and democratic values in society. The goal is to promote a better understanding and integration among European citizens and to help prevent the recurrence of any form of non-democratic rule in the future.